Embrionic and maggot’s development of Palaemon Elegans, living in Mingechaur and Shamkir water Reserviors in Azerbaijan Republic - L. V. Kulieva (Юг России: экология, развитие, 2015)
In article are presented results of the study of embryonic and maggot’s development of prawns Ralaemon elegans fished out from Shamkir and Mingechaur water reservoirs. There have studied of the reproductive possibility by specimen, as well as particularities of their feeding.